The Data Release of the Sloan Digital Sky Survey-II Supernova Survey. (14th May 2018) - Sako, Masao; Bassett, Bruce; Becker, Andrew C.; Brown, Peter J.; Campbell, Heather; Wolf, Rachel; Cinabro, David; D'Andrea, Chris B.; Dawson, Kyle S.; DeJongh, Fritz; Depoy, Darren L.; Dilday, Ben; et al.
Abstract: This paper describes the data release of the Sloan Digital Sky Survey-II (SDSS-II) Supernova Survey conducted between 2005 and 2007. Light curves, spectra, classifications, and ancillary data are presented for 10, 258 variable and transient sources discovered through repeat ugriz imaging of SDSS Stripe 82, a 300 deg 2 area along the celestial equator. This data release is comprised of all transient sources brighter than r ≃ 22.5 mag with no history of variability prior to 2004. Dedicated spectroscopic observations were performed on a subset of 889 transients, as well as spectra for thousands of transient host galaxies using the SDSS-III BOSS spectrographs. Photometric classifications are provided for the candidates with good multi-color light curves that were not observed spectroscopically, using host galaxy redshift information when available. From these observations, 4607 transients are either spectroscopically confirmed, or likely to be, supernovae, making this the largest sample of supernova candidates ever compiled. We present a new method for SN host-galaxy identification and derive host-galaxy properties including stellar masses, star formation rates, and the average stellar population ages from our SDSS multi-band photometry. We derive SALT2 distance moduli for a total of 1364 SN Ia with spectroscopic redshifts as well as photometric redshifts for a further 624 purely photometric SN Ia candidates. Using the spectroscopically confirmed subset of the three-year SDSS-II SN Ia sample and assuming a flat ΛCDM cosmology, we determine Ω M = 0.315 ± 0.093 (statistical error only) and detect a non-zero cosmological constant at 5.7 σ .